İş amaçlı havayolu pazarında hizmet kalitesinin servqual modeli ile ölçülmesi ve Türk Hava Yolları ‘Busıness Class’ yolcuları üzerine bir araştırma - (:unkn) unknown (My University, 2011)
Algılanan hizmet kalitesinin, müşteri tatmin düzeyi ve hizmetin yeniden müşterisi olma niyeti üzerindeki önemli etkisi; mevcut ve potansiyel müşterilerin hizmet kalitesi beklentilerinin ve algılarının nasıl ölçülebileceği konusunu, hizmet sektöründe faaliyet gösteren işletmelerinin en önemli kaygılarından birisi haline getirmiştir. Bu doğrultuda, hizmet sektörü içinde önemli bir ağırlığı olan havayolu sektöründe de müşteri beklentilerinin ve algılanan hizmet performansının etkin bir şekilde analiz edilerek hizmet kalitesinin ölçülebilmesi kritik önem taşımaktadır. Bu çerçevede bu araştırma; Türk Hava Yolları’nın iş amaçlı havayolu pazarında sunduğu hizmet kalitesini SERVQUAL Modeli ile ölçmeyi; yolcuların algılarını ve beklentilerini Fiziksel Varlıklar, Güvenilirlik, Karşılık Vermek, Güven ve Empati olarak belirlenen beş hizmet kalitesi boyutunda tespit etmeyi ve ihtiyaç duyulan boyutlar için iyileştirme önerilerini belirlemeyi amaçlamaktadır. Araştırma sonucunda elde edilen eşit ağırlıklı SERVQUAL skoru (-0.84) ve ağırlıklı SERVQUAL skoru (-0.17), negatif olmasına rağmen; her iki skorun da “0” değerine yakın olmaları göz önüne alındığında, Türk Hava Yolları’nın beklentileri karşılamaya oldukça yakın olduğu görülmektedir. SERVQUAL skorları boyutlar bazında değerlendirildiğinde; beş hizmet kalitesi boyutu içinde algı – beklenti farkının en düşük (-0,65) olduğu boyutun; hizmet isletmesinin sahip olduğu tesisler, ekipman ve teçhizat, donanım, personelin fiziksel özellikleri ve görünümü, hizmet sunumunda kullanılan araç-gereç ve diğer fiziksel donanımı içeren Fiziksel Özellikler boyutu olduğu tespit edilmiştir. Bu durum, Türk Hava Yolları’nın yolcuların beklentilerini karşılamaya en yakın olduğu hizmet kalitesi boyutunun, fiziksel özellikler boyutu olduğunu göstermektedir. Beş boyut içinde algı – beklenti farkının en yüksek (-1,04) olduğu boyutun ise; performansta tutarlılığı ve güvenilirliği, işletmenin söz konusu hizmeti ilk seferinde ve eksiksiz olarak yerine getirmesini ve verdiği taahhütlere sadık kalmasını ifade eden Güvenilirlik boyutu olduğu tespit edilmiştir. Güvenilirlik boyutunun, tahsis edilen önem skorları sıralamasında en yüksek değeri almış olması, bir diğer ifade ile yolcuların en fazla önem verdikleri boyut olması dikkate alındığında Türk Hava Yolları’nın en fazla iyileştirmeye ihtiyaç duyduğu hizmet kalitesi boyutunun Güvenilirlik boyutu olduğunu söylemek mümkündür.

Today, the service sector has become the most important segment of the world economy. The growth of the service sector not only offers business opportunities but also poses competitive threats for many service marketers. In today’s competitive business environment delivering superior service quality is a prerequisite for success and survival. The airline industry plays an important role in the growing service sector itself, as well as contributes significantly to other industries through the ability to transport passengers to their required locations all over the globe. With the rapidly changing and growing airline industry, the quality of airline service is a crucial factor of airliners’ success. The highly competitive market conditions in the airline industry pressurize airlines to deliver high-quality services. Thus, it is important for airlines to develop passenger-focused services by making an effort to understand passengers’ expectations and perceptions of service quality. To distinguish themselves from competitors, service business not only have to provide a better service, but also measure whether customers have a favorable evaluation of their service. Measuring quality perceptions permits service business to determine if customers are satisfied with service received; if inadequacies are identified, service business can implement strategies to correct such problems. After delivering the services, service business should monitor how well the customers’ expectations have been met. In accordance with this purpose, SERVQUAL is one of the best models for evaluating customers’ expectations and perceptions. SERVQUAL Model has been proposed as a valid and reliable model in airline service quality measurement. the SERVQUAL scale comprises 22 items to measure consumers’ service expectations (e.g., excellent airline companies will provide their services providers (e.g., Turkish Airlines will provide their services at the time they promise to do so). For each scale item, the difference between the expectation score and perception score is the gap score which reflects the service quality gaps. There are a total of 22 gap scores, given the 22-item scale. SERVQUAL Model include the five dimensions of service quality: (1) Tangibles (appearance of physical facilities, equipment, personnel, and communication materials); (2) Reliability (ability to perform the promised service dependably and accurately); (3) Responsiveness (willingness to help customers and provide prompt service) (4) Assurance (knowledge and courtesy of employees and their ability to convey trust and confidence; (5) Empathy (caring, individualized attention the firm provides its customers). The purpose of this research is to measure service quality that offered by Turkish Airlines in business air travel market by using SERVQUAL Model. The study aims to analyze the gaps between the passengers’ service expectations and actual service received and determine the dimensions of service quality which have needed to improve. In this research we also investigated the impact of demographic factors on passengers’ service perceptions. According to the research purpose, data were collected from the ‘Business Class’ passengers in Istanbul Ataturk International Airport. A self-administered questionnaire, an adapted version of SERVQUAL, was used in this study to analyze the service quality expectations and perceptions of the ‘Business Class’ passengers. The questionnaire divided into four parts, the first part consists of demographic information such as respondents' age, gender, occupation, educational level and number of flights in the past year. The second part was designed to measure the respondents’ expectations regarding quality of services offered by the airline companies. In the third part respondents allocated a total of 100 points among the five dimension according to how important each dimension is to them. Finally in the fourth part respondents provided their service quality perceptions according to the SERVQUAL scale. The questionnaires were distributed to passengers in person. Total of 270 questionnaires was collected, but after deleting 45 insufficient questionnaires, finally 225 questionnaires were used for the statistical analyses. The gender distribution was 24.4% female, 75.6% male. The highest proportion of the respondents (31.6%) fell into the 40–49 year age group, followed by the 30–39 year age group (27.1%). In terms of occupations the highest frequencies were manager (48.9%). The question on the educational level of passengers showed that 92% of the respondents had a university, college or graduate education. Regarding the respondents’ number of flights in the past year, a major part of the respondents reported that ten time or more (65.3.2%) number of flights in the past year. The results of this research indicate that that none of passengers’ perception responded to their expectations in any of dimensions. But in view of SERVQUAL scores (Unweighted SERVQUAL Score: -0,84; Weighed SERVQUAL Score: -0,17) it is possible to state that Turkish Airlines is very close to meet passengers’ expectations. An examination of the means of respondents perceptions based on the five dimensions of airline performance finds that ‘Business Class’ passengers of Turkish Airlines gave the highest rating to Assurance (mean 3.71), followed by Tangibles (mean 3.66), Responsiveness (mean 3.54), Reliability (mean 3.49), and Empathy (mean 3.37). They also have high expectations for airlines to perform well in Reliability (mean 4.52), followed by Assurance (mean 4.51), Responsiveness (mean 4.66), Tangibles (mean 3.31), and Empathy (mean 3.37). In terms of SERVQUAL scores (the difference between the expectation score and perception score) “tangibles” takes the lowest score and “reliability” has the highest. This means that for Turkish Airlines the tangible dimension of service quality is more likely to meet the expectations of customers. In other words ‘Business Class’ passengers were generally satisfied with appearance of physical facilities, equipment, personnel, and communication materials. But SERVQUAL score of “reliability” dimension indicate an important problem for Turkish Airlines. Because our findings suggest that “reliability” dimension is the most important service quality dimension. Turkish Airlines should give priority to perform the promised service dependably and accurately and show a sincere interest in solving problems of customers. This finding confirms that airline management should be more committed to performance improvement throughout the service delivery processes. To provide this, airline firms must first understand customers’ needs and expectations. Next, they should focus on how to deliver the most convenient service to meet customers’ needs.
Measuring the service quality in business air travel market by using servqual model and a research on ‘Business Class’ passengers of Turkish Airlines